QuillBot Grammar Checker: The Ability to Evaluate Students' Writing Errors of English Essay - Fitria, Tira Nur (International Journal of Computer and Information System (IJCIS), 2025)
This research simulates the use of QuillBot Grammar Checker in assessing students' writing errors in English essays. This research is descriptive qualitative. QuillBot announces the availability and accessibility of a new grammar checker. QuillBot's grammar checker can help users (teachers/lecturers) check writing errors in grammar, punctuation, and spelling. The analysis shows that two examples of students’ essays are evaluated by QuillBot Premium. The 1st student’s essay shows 209 words with 21 errors. It consists of grammatical errors (word class) such as nouns, pronouns, prepositions, conjunctions, and adjectives. The 2nd student’s essay shows 161 words with 20 errors. It consists of grammatical errors (word class) such as nouns, pronouns, prepositions, conjunctions, adjectives, and interjections. Users can choose two options (replace or ignore). Replace means change the error words, while ignore means keep maintaining the words In using QuillBot, users type Quillbot in the Google search engine, log in if needed, several menus will appear, and click Grammar Checker. Write or copy the English essay that we want to check. Errors in writing will appear with red underlines completed by many words and the number of errors in an essay. If we want to click repair, select Fix All Errors. QuillBot utilizes Artificial Intelligence (AI) to automatically scan text for grammatical, punctuation, spelling, punctuation, and capitalization issues, highlighting them and allowing users to correct them individually or in bulk with a single click. Teachers/lecturers can use corrective evaluations by using QuillBot as an alternative online tool besides the popularity of Grammarly. Regarding the accuracy level of using QuillBot in evaluating students' writing errors, it may need to be improved. However, other online grammar check applications can be considered and tried besides evaluation manually.